FLUIDIZED BED DRYER WITH THE NOVAL ATTACHMENTS FOR THE STUDY OF ITS PERFORMANCES - V. SRINIVASAN, A. NAGARAJAN , K. CHITHIRAI MOHAN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Sugar cane bagasse is one of the biomass has high initial moisture content, the drying could be done using different type of dryers. To minimize the space occupied for the equipments used for the drying process a little known behavior of fluidized bed dryer was suggested. The influence of the high initial moisture content of the wet bagasse reduces the performance of fluidization. A solid circulation of bagasse particles has achieved with two dissimilar distributors and number of orifices associated with a mechanical stirrer to spread out and improve the fluidization. The removal of high moisture content by the performance of fluidization from the wet bagasse was to be done by the three input temperatures. At the increased input temperature, the drying rate achieved as high due to the faster heat and mass transfer rate. The dried bagasse particles have directly used as fuel and it does not require the process of separation of inert particles used as in binary mixture fluidization bed.